Model Pendidikan Berbasis Komunitas - Toni; Karim, Ajerin; Bahari, Yohanes; Warneri (CV. Kurnia Grup, 2024)
The phenomenon of high education costs is a reality that cannot be denied. Currently, education is often considered a